Hydrodynamic voltammetry with channel microband electrodes: The simulation of voltammetric waveshapes - Bidwell, M; Alden, J; Compton, R (1996)
The strongly implicit procedure and the multigrid method MGD1 are used to simulate the steady-state current-voltage response of channel electrodes, including under conditions where diffusional effects in the direction of flow are significant. Reversible, quasi-reversible and irreversible heterogeneous kinetics are all considered.